Effect of extender type and cold storage of fresh semen on reproductive indices of Karakul ewe following fixed time artificial insemination - HASHEMI, MAJID; SAFDARIAN, MAZAHER; HASHEMI, SEYED MOHAMMAD REZA (The Indian Journal of Animal Sciences, 2018)
Semen quantity and quality are affected by transportation and frequent semen collection in ram when they are transported from nucleus flock to target farms for in situ artificial insemination (AI) of ewes with fresh semen. The current study was designed to introduce the best method of fresh semen preservation for fixed time AI in Karakul sheep. The adult Karakul ewes were allocated to 6 groups (30 ewes in each group) during the breeding season and each group was inseminated with one of the following treatments, viz. fresh semen without extender, fresh semen diluted with Tris-egg yolk or milk, cooled semen (stored at 10°C for 8 h) without extender, and cooled semen diluted with Tris-egg yolk or milk. Lambing and fecundity rates were the highest when ewe was inseminated with undiluted fresh semen (71.42 and 85.71%, respectively). These reproductive indices in ewes, which were inseminated with diluted fresh semen or undiluted cooled semen were significantly lower than those recorded in inseminated ewes with undiluted fresh semen. The type of extender and storage of diluted semen at 10°C for 8 h did not significantly affect lambing rate of Karakul ewe. Results suggested that use of undiluted fresh semen and diluted fresh semen in milk or Tris-egg yolk extenders are preferable for fixed time AI in ewes of genetic improvement center and Karakul sheep flocks located near to this center, respectively.